GC-MS-Based metabolite profiling of Salacca zalacca flesh extracts obtained by different extraction methods and their inhibitor activity on alpha-glucosidase - Dzatil Awanis Mohd Bukhari (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2018)
Present study was performed to explore the potential of Salacca zalacca flesh extracts as α-glucosidase inhibitor; which is one of the anti-diabetic agents used to manage the disease. This study aimed to obtain extracts of Salacca zalacca flesh by using three extraction methods – Soxhlet extraction (SE), supercritical fluid extraction (SFE) and ultrasound-assisted extraction (UAE). All extracts obtained were then subjected to GC-MS-based metabolite profiling and their in vitro α-glucosidase inhibitory assay. Different extraction methods were employed in this study to determine the most appropriate method and extraction condition in drawing out desired bioactive compounds from the plant sample. The results showed the highest extraction yield was obtained by 50% ethanol extract of SE (73.2 ± 4.4%), whereas SFE_1 showed the lowest yield (0.42 ± 0.08%). Besides, overall extraction yield suggested that both factors – extraction method and solvent type had significantly influenced the outcome. Following that, all extracts were evaluated for in vitro α-glucosidase inhibitory activity, measured by their IC50 values in comparison to that of quercetin, the positive control (IC50 = 2.7 ± 0.7 μg/mL). The lowest α-glucosidase inhibitory activity was indicated by water extract of SE (IC50 = 724.3 ± 13.15 μg/mL) and the highest activity was demonstrated by 60% ethanol extract of UAE (IC50 = 16.3 ± 1.3 μg/mL). The in vitro assay of α-glucosidase inhibitory activity was performed in microtiter plates, which are well acknowledged as fast, robust, cost-effective and reproducible method. Subsequently, all extracts including active and inactive ones were analysed by GC-MS to identify metabolites that may possess the potential as α-glucosidase inhibitor. Carbohydrates, fatty acids, organic acids, phenolic acids, sterols and alkane-based compounds were identified from active UAE and SFE extracts. The list of identified metabolites was compared with the previously reported metabolites with significant α-glucosidase inhibitory activity such as citric acid, palmitic acid, stearic acid, linoleic acid, oleic acid, 9-octadecenoic acid, gallic acid, stigmasterol and β-sitosterol. Hence, the reported activity against α-glucosidase enzyme might be attributable to the presence of these metabolites. As a conclusion, this study explored the key potential of S. zalacca flesh extract as α-glucosidase inhibitor.